Effect of Oxytetracycline Treatment on Postpartum Reproductive Performance in Dairy Buffalo-Cows with Retained Placenta in Egypt - A Gohar, Mohamed; A Elmetwally, Mohammed; Montaser, Abdelmonem; M. Zaabel, Samy (Journal of Veterinary Healthcare, 2018)
Retained fetal membrane (RFM) is a crucial calving related disorder that affects economic for the farmer and herd health. Retention of Placenta (ROP) is the condition in which the fetal membranes are not expelled within a period of 12 hours after parturition. Buffalo cows (n=34) aged 4-9 years old with 2-6 lactation season were used in the present study. The Experimental buffaloes were divided into either with (n=25) or without (n=9) fetal membrane retention. The objective of this study was to evaluate the effect of oxytetracycline treatment on reproductive performance of buffalo-cows with retained fetal membranes. All buffaloes in treated group received systemic infusion of oxytetracyclin Hcl injection 5% and 10 mg/kg oxytetracycline for 3 days intrauterine. Reproductive performance parameters for all experimental buffaloes were days to first estrous, number of service per conception, days open and pregnancy diagnosis. All reproductive parameters demonstrated significant changes between treated and non-treated animals (P < 0.05). Altogether, the obtained results indicated that retained placenta in buffaloes could be treated successfully by intrauterine infusion of oxytetracycline
Keywords: buffalo-cows; retention placenta; oxytetracycline; reproductive performance